Transcriptional regulation of secondary metabolism and autophagy genes in response to DNA replication stress in Setosphaeria turcica - Ya-nan MENG; Xin-jie ZHANG; Fan-li ZENG; Wei-bo ZHAI; Pan LI; Jing-jing HU; Sheng-lin XIAO; Zhi-min HAO; Zhi-yan CAO; Chuan CHEN; Jin-gao DONG (Journal of Integrative Agriculture, 2023)
The fungal pathogen Setosphaeria turcica causes northern corn leaf blight (NCLB), which leads to considerable crop losses. Setosphaeria turcica elaborates a specialized infection structures called appressorium for maize infection. Previously, we demonstrated that the S. turcica triggers an S-phase checkpoint and ATR (Ataxia Telangiectasia and Rad3 related)-dependent self-protective response to DNA genotoxic insults during maize infection. However, how the regulatory mechanism works was still largely unknown. Here, we report a genome wide transcriptional profile analysis during appressorium formation in the present of DNA replication stress. We performed RNA-Seq analysis to identify S. tuicica genes responsive to DNA replication stress. In the current work, we found that appressorium-mediated maize infection by S. turcica is significantly blocked by S-phase checkpoint. A large serial of secondary metabolite and melanin biosynthesis genes were blocked in appressorium formation of S. turcica during the replication stress. The secondary metabolite biosynthesis genes including alcohol dehydrogenase GroES-like domain, multicopper oxidase, ABC-transporter families, cytochrome P450 and FAD-containing monooxygenase were related to plant pathogen infection. In addition, we demonstrated that autophagy in S. turcica is up-regulated by ATR as a defense response to stress. We identified StATG3, StATG4, StATG5, StATG7 and StATG16 genes for autophagy were induced by ATR-mediated S-phase checkpoint. We therefore propose that in response to genotoxic stress, S. turcica utilizes ATR-dependent pathway to turn off transcription of genes governing appressorium-mediated infection, and meanwhile inducing transcription of autophagy genes likely as a mechanism of self-protection, aside from the more conservative responses in eukaryotes.